Los ejes transversales y su incidencia en el aprendizaje significativo de los estudiantes de 4to a séptimo año, en la escuela de educación básica “Agustín Albán” del cantón Pujilì, en el año lectivo 2014/2015 - Chasiloa Chuquitarco, Mayra Alexandra (2015)
In the present research it was made a quick detailed analysis about the application of curricular transversal axis in the making of the student’s significant learning of fourth to seventh year of basic education “Agustin Alban” of Pujilí School. The transversal axis are interdisciplinary tools those promote the interrelation between education sector and society strengthening values as ethical as moral, the application of the axis allow maintaining a democratic coexistence, integral formation , framed in responsibility. The problems of modern society show the necessity to create citizen to with full moral values whit the capacity to solve problems. Research Carrie out represents a number of strategic activities those improved student`s knowledge management of that institution, under this context it proposes the elaboration of a didactic guide that it will allow to help students to know the transversal axis in the construction of the significant learning. The research generated positive changes in students will develop active participation rousing in them the interest, attention and motivation in class facilitating teacher`s work, therefore transversal axis become necessary’s instruments to improve teaching learning process.